Evaluasi Open Goverment Pada Layanan Perizinan Online Di DPM PTSP Kota Palangkaraya - Rusita, Rusita; Sadar, Sadar; Satia, Riban (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The application of Open Government principles in online licensing services aims to increase transparency, participation, and accountability in public services. This study evaluates Open Government in online licensing services at the Palangka Raya City Investment and One-Stop Integrated Services Agency (DPMPTSP) through the Online Single Submission (OSS) system. Using a qualitative descriptive approach, the study analyzed six key aspects based on William N. Dunn's evaluation theory: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The research findings indicate that the OSS system successfully increased the efficiency of the licensing process with fast turnaround times (1-5 days) and more open access to information, supported by outreach and technical assistance. However, challenges such as low digital literacy among the public (especially the elderly), gaps in technology access, and delays in verification still hamper optimization. These results emphasize the need for improved digital infrastructure, human resource training, and inclusive outreach to strengthen the implementation of Open Government principles.